2022
DOI: 10.1038/s41598-022-24417-w
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the cognitive states of attention and distraction in a real-life setting using EEG

Abstract: Lapses in attention can have serious consequences in situations such as driving a car, hence there is considerable interest in tracking it using neural measures. However, as most of these studies have been done in highly controlled and artificial laboratory settings, we want to explore whether it is also possible to determine attention and distraction using electroencephalogram (EEG) data collected in a natural setting using machine/deep learning. 24 participants volunteered for the study. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Indeed, we found that Tibetan monastic debate is associated with an increase in frontal midline theta oscillations (van Vugt et al 2020), which are also found in other meditation practices and thought to reflect attentional focus. Moreover, we found that more experienced monks spend less time distracted than less experienced monks during monastic debate (Kaushik et al 2022).…”
Section: Testable Hypotheses For Future Experimentsmentioning
confidence: 59%
“…Indeed, we found that Tibetan monastic debate is associated with an increase in frontal midline theta oscillations (van Vugt et al 2020), which are also found in other meditation practices and thought to reflect attentional focus. Moreover, we found that more experienced monks spend less time distracted than less experienced monks during monastic debate (Kaushik et al 2022).…”
Section: Testable Hypotheses For Future Experimentsmentioning
confidence: 59%
“…We separately tested decoding performance using different frequency bands, which may subserve different functional roles during mind wandering ( Kam et al, 2022 ), and we observed that beta band gave the highest prediction performance among the 4 frequency bands in both classification pipelines. Kaushik et al (2022) reported theta and alpha gave the highest performance. Dhindsa et al (2019) compared alpha, theta, and beta band (beta1:13–18 Hz, and beta2: 19–30 Hz), and their results showed that beta band (both beta1 and beta2) had the highest performance in a portion of the participants.…”
Section: Discussionmentioning
confidence: 97%
“…The 2-s window was based on a trade-off between better feature extraction with longer windows versus the need for real-time decoding with shorter windows. The choice of a 2-s window duration is consistent with the approach taken by Kaushik et al (2022) . The segments from the focused learning condition were labeled as non-mind wandering and segments from the future planning condition were labeled mind wandering (2-class).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations